2004
DOI: 10.1109/tns.2003.823027
|View full text |Cite
|
Sign up to set email alerts
|

Registration and fusion of SPECT, high-resolution MRI, and interventional MRI for thermal ablation of prostate cancer

Abstract: Abstract-We are investigating interventional MRI (iMRI) guided radiofrequency thermal ablation for the minimally invasive treatment of the prostate cancer. Nuclear medicine can detect and localize tumor in the prostate not reliably seen in MRI. We intend to combine the advantages of functional images such as nuclear medicine SPECT with iMRI-guided treatments. Our concept is to first register the low-resolution SPECT with a high-resolution MRI volume. Then by registering the high-resolution MR image with live-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…(1) We first register the MR images with the preliminary reconstruction of PET data using the mutual informationbased registration methods developed in our lab. [22][23][24][25][26][27][28] (2) The skull tissue is segmented on the MR images using our segmentation method as described below. (WM), and cerebrospinal fluid (CSF).…”
Section: Iic Overview Of the Mr/pet Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) We first register the MR images with the preliminary reconstruction of PET data using the mutual informationbased registration methods developed in our lab. [22][23][24][25][26][27][28] (2) The skull tissue is segmented on the MR images using our segmentation method as described below. (WM), and cerebrospinal fluid (CSF).…”
Section: Iic Overview Of the Mr/pet Data Processingmentioning
confidence: 99%
“…The voxel size was 1.0 × 1.0 × 1.6 mm 3 . We registered the CT to the corresponding MR images using the registration methods [22][23][24][25][26][27][28] that have been evaluated in our laboratory. On the CT images, we used a threshold method to obtain the skull and the results provide the ground truth of the skull for the evaluation of the MR image segmentation.…”
Section: Iig1 Segmentation Evaluationmentioning
confidence: 99%
“…Before we close our discussion on MRI-based methods, it should be noted that currently MRI-based techniques are in use for PCa computer-aided treatment procedures such as: MRI-guided radio-frequency thermal ablation of PCa (Fei et al 2003(Fei et al , 2004, planning of the radiotherapy treatment and quality control of the correct placement of radioactive seeds in prostate brachytherapy (postimplant dosimetric analysis) (Van Gellekom et al 2004;Prete et al 1998;Susil et al2004). Therapeutic methods are beyond the scope of the present survey.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…We have found that rendering one image in gray and the other in red with a manually adjustable transparency scale, provides a very good way to visually determine registration accuracy. 36 (2) We used a checkerboard display whereby we divided the reference and registered images into sectors and created an output image by alternating sectors from the two input images. 37 Even small shifts of edges therefore are clearly visible.…”
Section: Registration Evaluationmentioning
confidence: 99%